National Study of Fournier Gangrene in Spain (2016–2021): Gender/Sex Differences in Mortality and Risks - Isabel Belinchón-Romer; Alberto Ramos-Belinchón; Ester Lobato-Martínez; Verónica Sánchez-García; José-Manuel Ramos-Rincón (Medicina)
Background and Objective: The aim of this study was to analyze sex differences in risk factors associated with hospital mortality in patients with Fournier gangrene (FG). Materials and Methods: A retrospective population-based study (2016–2021) included FG hospitalizations in Spain. To identify the risk factors, we used multivariable logistic regression and reported adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Results: There were 3644 admissions for FG during the study period (82.5% men and 17.5% women). The mean hospitalization rate per 1000 admissions/year was 0.23 for men and 0.05 for women, and the mean hospitalization rate per 100,000 inhabitants/year was 2.7 for men and 0.4 in women. The most common comorbidities were hypertension (44.9%) and diabetes mellitus (35.6%). The main complications were sepsis (22.1%), 29.8% were admitted to the intensive care unit and 16.1% died. Mortality was higher in women (aOR 1.32, 95% CI 1.07–1.63). The main independent risk factors for mortality in the entire sample were older age, neoplasms, chronic kidney disease, heart failure, sepsis, acute kidney injury, and admission to the intensive care unit. In women, they were older age, leukemia, sepsis, acute kidney injury, and admission to the intensive care unit. Conclusions: The overall FG mortality rate was slightly higher in women than in men, people aged >64 years, people with chronic kidney disease, sepsis, and acute kidney injury, and admission to the intensive care unit. The independent factors associated with mortality in women were similar in both sexes.